A New Paradigm in the Logistic and Similar Maps: Time Stepping Schemes - Lizama-Yanez, C (Springer-Verlag Italia s.r.l., 2024)
We propose the qualitative mathematical analysis of discrete models by replacing the classical Euler scheme of order 1 with Lubich quadrature time-stepping schemes. As the first study with this new paradigm, we compare the bifurcation diagrams for the logistic and sine maps obtained from discretizations of orders 1, 2, and 1/2. © The Author(s) under exclusive licence to The Royal Academy of Sciences, Madrid 2024.